Ionospheric anomalies preceding the low-latitude earthquake that occurred on April 16, 2016 in Ecuador - Sotomayor Beltran, Carlos (2019)
A catastrophic seismic event of M w 7.8 occurred on April 16, 2016 in Ecuador. As with some other major earthquakes, many human lives were lost. Thus in the last two decades, the search for seismo-ionospheric signatures has become an active field of research. In order to provide further insights into ionospheric precursors of earthquakes, Global Ionospheric Maps (GIMs) provided by the Center for Orbit Determination in Europe (CODE) were used to look for ionospheric anomalies prior to the earthquake in Ecuador. By producing differential Vertical Total Electron Content (VTEC) maps and using a statistical method, a negative ionospheric anomaly was observed 10 days before the incident. At different confidence levels the negative disturbance was permanently visible. This anomaly also is located within the earthquake preparation zone, defined by the Dobrovolsky equation. Additionally, due to the extreme low-latitude nature of the earthquake, the dynamics of the Equatorial Ionization Anomaly (EIA) shape were observed. A further confirmation of the ionospheric anomaly was provided by the dramatic change of the EIA 10 days before the earthquake with respect to a non-disturbed day. Due to the really quiet geomagnetic and solar conditions for April 6, 2016, the negative anomaly is considered to be a seismo-ionospheric signature.